2008
DOI: 10.1007/s10404-008-0349-6
|View full text |Cite
|
Sign up to set email alerts
|

A liquid film motor

Abstract: It is well known that electro-hydrodynamical effects in freely suspended liquid films can force liquids to flow. Here, we report a purely electrically driven rotation in water and some other liquid suspended films with full control on the velocity and the chirality of the rotating vortices. The device, which is called ''film motor'', consists of a quasi two-dimensional electrolysis cell in an external in-plane electric field, crossing the mean electrolysis current density. If either the external field or the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
60
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 14 publications
2
60
0
Order By: Relevance
“…For a suspended film of liquid, which was called a liquid film motor, 19,20 the same results were reported. When the free surface of the polar liquid is covered with a nonpolar thin film, the rotation dies.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…For a suspended film of liquid, which was called a liquid film motor, 19,20 the same results were reported. When the free surface of the polar liquid is covered with a nonpolar thin film, the rotation dies.…”
mentioning
confidence: 58%
“…Amjadi et al have shown that applying a uniform electric field to a water film (soap solution), which possesses a uniform electric current, produces a controllable rotating flow in the film. 19,20 The controllable rotation of a fluid film has also been reported for polar liquid films 19,20 and MBBA liquid crystal films. 21 In all of these cases, the rotation of a thin suspended film of fluid was studied.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Morris et al 15,16 suggested that it is the electric charges accumulated on the surface of suspended lms that produce such instabilities. Amjadi et al [17][18][19] proposed a method for controlling the rotational ow on thin suspended liquid lms demonstrating that a simultaneous application of an electric eld and an electric current produces controllable rotations in a suspended liquid lm. Such an instability has been studied theoretically by Liu et al 20,21 and Nasiri et al 22 and the rotation mechanism was explained by Feiz et al using a thin lm electro-convection model.…”
Section: -9mentioning
confidence: 99%